Pediatric screen exposure and school related headache disability. (November 2022) - Langdon, Raquel; Mandel, Alexandra; Cameron, Mark; Pierce, Emily; McCracken, Emily; Strelzik, Jeffrey; McClintock, William; Bost, James; DiSabella, Marc
Background and Objectives: Prolonged screen exposure is often cited as a trigger for pediatric headache. We present initial findings evaluating the association between adolescent screen use type, duration, and school disability. Methods: New patients aged 12–17 years presenting to a headache clinic were screened and surveyed regarding headache characteristics, behavioral habits, school attendance, and screen utilization. Results: 99 adolescents (29 M, 70 F) with average age 14.8 years and average headache frequency of 17 days per month completed the survey. Patients missed an average of five full days and three partial days of school due to headaches over the 90 days prior to survey completion. No statistically significant correlation was found between type or duration of screen exposure and monthly headache frequency, school attendance, or school functioning. A small positive association was seen between increasing duration of computer use, total hours screen use, and school absenteeism. While most adolescents reported prolonged screen use (58.6%) and luminosity (64.6%) worsened headaches, no statistical difference was seen in average number of headache days per month. Conclusions: Average monthly headache frequency in an adolescent population was not significantly correlated with type or duration of screen exposure. Further studies are needed to elucidate how screen utilization impacts school related headache disability.